The Effects of Different Calcination Parameters on CCTO Formation - Julie J., Mohamed; M. M., Noor (2008)
Dielectric material CaCu3Ti4O12 (CCTO) was prepared by solid state technique. CaCO3, TiO2 and CuO powders were mixed thoroughly in a ball mill for an hour. The mixed powder was calcined at 800 and 900oC for different durations. The calcined samples were subjected to XRD phase analysis and SEM observation. All the samples were sintered at 1050 oC for 24 hours, before dielectric constant measurement was done. The effects of different calcination parameters on phase formation, microstructures, and dielectric constant were reported. XRD results show the different phase formations, and the CCTO single phase was first detected for the sample calcined at 900 oC for 6 hours. Increasing the temperature and duration enhances the density, dielectric constant value and the grain growth was observed. The CCTO single phase with the highest dielectric constant was obtained by calcination at 900oC for 12 hours.